Effects of low-intensity ultrasound opening the blood-brain barrier on Alzheimer's disease—a mini review - Mengmeng Zhou; Xuanhao Fu; Boyuan Ma; Ziyu Chen; Yuelin Cheng; Linyan Liu; Shunli Kan; Xinyan Zhao; Sa Feng; Zehua Jiang; Rusen Zhu (Frontiers in Neurology, 2023)
Due to the complex pathological mechanisms of Alzheimer's disease (AD), its treatment remains a challenge. One of the major difficulties in treating AD is the difficulty for drugs to cross the blood–brain barrier (BBB). Low-intensity ultrasound (LIUS) is a novel type of ultrasound with neuromodulation function. It has been widely reported that LIUS combined with intravenous injection of microbubbles (MB) can effectively, safely, and reversibly open the BBB to achieve non-invasive targeted drug delivery. However, many studies have reported that LIUS combined with MB-mediated BBB opening (LIUS + MB-BBBO) can improve pathological deposition and cognitive impairment in AD patients and mice without delivering additional drugs. This article reviews the relevant research studies on LIUS + MB-BBBO in the treatment of AD, analyzes its potential mechanisms, and summarizes relevant ultrasound parameters.